APLIKASI PERMAINAN KARTU MEMORI BERBASIS WEB UNTUK PEMBELAJARAN KOSAKATA BAHASA SUNDA (STUDI KASUS SEKOLAH DASAR NEGERI BINAWARGA CIPONGKOR) - Ridwan Nur Hakim; Dini Rohmayani (IPSIKOM, 2025)
In today's digital era, technology-based learning is an important need, especially in maintaining the use of regional languages such as Sundanese which are increasingly rarely used in everyday life. This study aims to design, implement, and test a web-based memory card game application as a medium for learning Sundanese vocabulary for elementary school students. The development method used is the waterfall model which includes the stages of analysis, design, implementation, testing, deployment, and maintenance. This application was developed using React with Tailwind CSS for the frontend, Node.js with Express JS, and PostgreSQL as the database. The main features provided include difficulty level selection, point system, leaderboard, and vocabulary and student data management by the admin. The results of black box testing all features have run 100% according to their functions, and the results of User Acceptance Testing (UAT) from 3 testing parameters namely features, design, and user satisfaction show a very positive response from teachers with a satisfaction level of 95.1% and from students of 74.6%. These findings show that the application can be well received by users and is able to increase students' interest in learning Sundanese language.